Aclimatación de plántulas de piñón (Jatropha curcasL.) propagadas in vitro en la estación experimental agraria El Porvenir Juan Guerra - Mas Golac, Rober Anstrong (2013)
With the aim of developing a methodology of acclimatization of seedlings of pine nut (Jatropha curcas L.) cultivated in vitro from Zygotic embryos, studied 3 (1, 2 and 3 ppm) concentrations of two inductors of growth (AIB and ANA) and 3 levels of electrical conductivity of a solution of plant fertilizer (1,6; 2,2 and 2,8 mmhos) in pine seedlings propagated in vitro of 28 days in an atmosphere of incubation with a dimmable 10,76-2 734 lux, temperature 17,9 – 25,17 ° C, relative humidity of 30,2 – 41,7%, and a photoperiod of 16 hours light and 8 hours of darkness, with 30 days of acclimatization in an atmosphere of 21,71 pre – 36,57 º C temperature, 38,1 – 99,8% of relative humidity and 10,76 – 1 862 lux of light intensity, using a block with factorial arrangement design. The percentage of survival of seedlings in the phase of acclimatization this influenced by growth inducers and concentrations acting like forms with a percentage of survival from 94,18 and 95,90%. The height of seedling in the phase of acclimatization influenced by the interaction of the indole butyric acid at a concentration of 3 ppm. The diameter of stem of seedlings in the phase of acclimatization influenced by growth inducer acid indole butyric (A2), obtaining a 0,83 average stem diameter cm. The area leaf seedlings in the phase of acclimatization is influenced by the interaction of inductors for growth, concentrations and the electrical conductivity of the foliar fertilizer (ABC), inductor acid Naftalenacetico to 2 and 3 ppm concentrations and conductivity of 2,8 foliar fertilizer mmhos has greater effect should be used with an average of 23,68 area cm2 . The length of roots of seedlings of pine nut (Jatropha curca L.) in the phase of acclimatization this influenced by the inductors of growth (ANA and AIB) at a concentration of 2-3 ppm and electrical conductivity of the foliar fertilizer of 2,2 and 2,8 mmhos. The length of peduncle of a seedling in the phase of acclimatization this influenced by (A1 and A2) growth inducers, to a concentration of 3ppm and electrical conductivity of 3 mmhos.The weight of fresh biomass of seedlings this influenced by the inductors of growth (ANA and AIB), at a concentration of 1 ppm and electrical conductivity of the foliar fertilizer 2,8 mmhos. The dry matter of the seedlings in the phase of acclimatization depends on the inducer of growth AIB to a concentration of 1ppm and electrical conductivity of 2,8 mmhos.